Crumbs/DaPKC-Dependent Apical Exclusion of Bazooka Promotes Photoreceptor Polarity Remodeling. - Walther, R.F.; Pichaud, F. (Current Biology, 2010)
In Drosophila epithelial cells, specification and maintenance of the zonula adherens (za) is crucial to ensure epithelial tissue integrity. This depends on the intertwined function of Bazooka (Baz), Par6-DaPKC, and the Crumbs (Crb)-Stardust (Sdt)-PATJ complex. However, the detailed molecular basis for the interplay between these factors during this process is not fully understood.We demonstrate that during photoreceptor apicobasal polarity remodeling, Crb is required to exclude Baz from the subapical domain. This is achieved by recruiting Par6 and DaPKC to this membrane domain. This molecular sorting depends on Baz phosphorylation by DaPKC at the conserved serine 980 and on the activity of the small GTPase Cdc42 associated with Par6. Our data indicate that although Cdc42 binding to Par6 is not required for Baz phosphorylation by DaPKC, it is required for optimum recruitment of Crb at the subapical membrane, a process necessary for delineating the nascent za from this membrane domain.Binding of Cdc42 to the DaPKC regulatory subunit Par6 is required to promote Crb- and DaPKC-dependent apical exclusion of Baz. This molecular sorting mechanism results in setting up the boundary between the photoreceptor subapical membrane and the za.